Vertical video: rupturing the aesthetic paradigm. (May 2018) - Ryan, Kathleen M
Popular culture has critiqued 'vertical video syndrome', or video shot on smartphones in the portrait rather than landscape orientation, as something aesthetically unpleasing which should be avoided. But the design of smartphones seems to encourage shooting vertical video. This article examines the aesthetic desirability of vertical videos through applied media aesthetics. It traces the history of horizontal film and television orientations, as well as the image-centric orientation model found in still photography. It argues that vertical video, rather than a syndrome to be avoided, instead takes advantage of the technological innovations and embodied pleasures offered by the smartphone to rupture the visual paradigms and create a new visual aesthetic for phone-based moving images.